Psychological factors and long-term tinnitus handicap in vestibular schwannoma patients after retrosigmoid microsurgery–a cross-sectional study - Thomas, M.; Scheer, M.; Rampp, S.; Strauss, C.; Schönfeld, R.; Leplow, B. (International Journal of Audiology, 2024)
Objective: This study aimed to investigate the connection between psychological factors and postoperative tinnitus in vestibular schwannoma (VS) patients following retrosigmoid microsurgery. Design: Cross-sectional study. Study sample: Ninety-three VS patients participated, completing questionnaires on demographics, tinnitus severity (THI-12), personality traits (TIPI-G), dizziness impact (DHI), perceived health benefits (GBI), somatisation tendencies (SOMS-2), and psychological distress (HADS-D). Our analysis involved Mann-Whitney U-tests, Spearman’s rank-order correlations, and false discovery rate correction. Results: Most participants reported postoperative tinnitus (77/93), with 41 experiencing it preoperatively. Emotional stability correlated negatively with tinnitus presence, while tinnitus severity was associated with emotional distress. Preoperative somatisation tendencies were also positively linked to tinnitus severity. Postoperative Tinnitus was further linked to reduced perceived health benefits and increased anxiety and depression levels. Notably, age and gender showed no significant associations. Conclusion: This study uncovers the interplay between postoperative tinnitus and psychological factors in VS patients, highlighting emotional and cognitive dimensions. Tailored psychological interventions addressing tinnitus‘s psychosomatic impact may enhance patients quality of life.
CRIS-Team Scopus Importer:2024-05-17
Keywords: dizziness; microsurgery; personality; psychological factors; tinnitus; Vestibular schwannoma